Integrasi Teknologi Pendidikan dalam Kurikulum Pesantren: Analisis Konseptual melalui Kerangka TPACK dan SAMR - Hafizh Raafi; Ahmad Saifulloh (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to develop a conceptual model of a digital-adaptive pesantren curriculum by synthesizing the characteristics of pesantren curricula and integrating the Technological Pedagogical Content Knowledge (TPACK) and Substitution, Augmentation, Modification, and Redefinition (SAMR) frameworks. The rapid advancement of digital technology has created significant challenges for Islamic boarding schools (pesantren) in maintaining their educational identity while responding to the demands of twenty-first-century education. This study employed a qualitative approach using a library research method by reviewing and synthesizing relevant national and international literature on Islamic education, curriculum development, educational technology, TPACK, and SAMR. The findings reveal that pesantren curricula have evolved from traditional (salaf) and modern models toward an integrative curriculum that combines Islamic values, scientific knowledge, digital technology, and twenty-first-century competencies. The proposed conceptual model consists of four interconnected components: (1) foundational values based on the Qur'an, Hadith, and pesantren traditions; (2) core competencies comprising religious competence, digital competence, and global competence; (3) curriculum development frameworks integrating TPACK and SAMR; and (4) expected outcomes in the form of religious, digitally literate, and adaptive graduates. The study contributes theoretically by enriching the discourse on Islamic curriculum development through an integrative framework that bridges the traditional epistemology of pesantren with contemporary digital learning theories. Practically, the proposed model provides strategic guidance for curriculum developers, educators, pesantren leaders, and policymakers in designing adaptive Islamic education that preserves pesantren values while strengthening digital literacy, ethical technology integration, and graduates' readiness to address the challenges of the digital era.